Šolska knjižnica kot prostor za razvijanje socialnih veščin - Zwitter, Savina (Knjižnica, 2019)
The article follows the theme of library buildings and space and concentrates on a school library, where several different activities helping to develop various users' skills take place. It focuses on those school library activities that help to develop social skills. Here, we observe that one of the key points is the space, which should be big enough to allow study, working and free-time social activities going on simultaneously, which is not possible if the space is too small. The issues discussed start from the theoretical standpoints and the experiences in the school offering both national and international curricul. Each of them has different demands and expectations and helps to develop social skills in its own way. Since each school is specific, the articles' aim is to present the reader with the ideas, which the librarians can adapt for their own purpose and abilities or develop further.
Keywords: dijaki; gimnazije; mednarodni programi; socialne veščine; šolske knjižnice